The Comprehensive Systematic Review of Use of Prostaglandin Analogues in Glaucoma Treatment - Irene Sekarjati (The International Journal of Medical Science and Health Research, 2026)
Introduction: Glaucoma is a leading cause of irreversible blindness worldwide, characterized by progressive optic neuropathy, with elevated intraocular pressure (IOP) being the primary modifiable risk factor. Prostaglandin analogues (PGAs) have emerged as a cornerstone of pharmacological therapy due to their potent IOP-lowering efficacy and once-daily dosing (Aptel, Cucherat & Denis, 2008). This systematic review synthesizes evidence on the efficacy, safety, and clinical utility of PGAs in glaucoma management. Methods: A systematic literature review was conducted. We screened studies based on predefined criteria, including human studies on adult glaucoma patients, evaluation of PGA interventions, reporting of clinical outcomes (IOP reduction, visual field, adverse events), and acceptable study designs (RCTs, cohort studies, systematic reviews, etc.). Data from 80 included sources were extracted concerning study design, patient population, interventions, IOP efficacy, safety profiles, and key conclusions. Results: PGAs consistently demonstrated substantial IOP reduction, with bimatoprost often showing numerically superior efficacy (mean reduction up to 9.16 mmHg, 35.2%) compared to latanoprost (7.7 mmHg, 31%) and travoprost (8.0-8.9 mmHg) (Brandt et al., 2001; Hedman & Alm, 2000). The United Kingdom Glaucoma Treatment Study (UKGTS) provided pivotal evidence that latanoprost significantly reduces the risk of visual field deterioration compared to placebo (Hazard Ratio 0.44) (Garway-Heath et al., 2015). Safety profiles varied, with bimatoprost associated with the highest incidence of conjunctival hyperemia, while latanoprost was generally better tolerated (Aptel, Cucherat & Denis, 2008). Novel formulations like latanoprostene bunod and preservative-free PGAs offered enhanced efficacy or improved tolerability (Weinreb et al., 2017; Hommer et al., 2010). Discussion: The analysis reveals a critical trade-off between the maximal IOP-lowering potential of bimatoprost and the superior tolerability of latanoprost. Long-term efficacy is maintained, and PGAs are effective in special populations like normal-tension and angle-closure glaucoma. Preservative-free formulations address ocular surface disease concerns, potentially improving adherence. Conclusion: Prostaglandin analogues remain the first-line pharmacological treatment for glaucoma, offering effective and sustained IOP reduction. Clinical choice should individualize therapy based on the required IOP target, patient tolerance, and ocular surface health. Future research should focus on long-term comparative outcomes, personalized medicine approaches, and novel drug delivery systems.